Determination of the Tail Unit Parameters of Ultralight Manned and Unmanned Helicopters at the Preliminary Design Stage - Vitaly Dudnik (Aerospace)
The 1–2 seat helicopters have developed considerably in recent years. They have a maximum take-off weight of 250 to 750 kg. Most of these helicopters have been converted into unmanned versions. Typically, such UAV models retain the rotor system, power plant, transmission, and empennage of the manned versions. For this reason, statistics and design methods for small manned helicopters are also applied to unmanned versions. The existing methods for selecting helicopter parameters in the preliminary design phase are based on statistical data for heavier-class helicopters. However, the lightest weight class helicopters differ significantly from their heavier counterparts. The analysis shows that the results of parameter selection at the preliminary design stage have an error rate of between 11 and 30%. The main reason for this difference is a scale factor. In this paper, a method for determining helicopter tail unit parameters at the preliminary design stage is presented. The proposed relationships for the horizontal stabilizer, fin, tail boom, and tail rotor parameters are based on an analysis of statistical data from 36 rotorcraft and the author’s design experience. In particular, the article presents the relationships between the geometric parameters of the empennage and tail rotor from other helicopter data. The relationships presented also allow the mass of the tail unit to be determined.